(3OjhGf GHf GdfHjgs - (3GHf GdfHjg , Ydj Hf eMeO Hf GdMSf Hf jhSa, ceGd GdOjf CHh GdMSf,J (B619 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi HK CQhGM GdYbhd ai CLSGO GdUhQ s
(3BNQgG (B:s
(3hGgG ceMi GdJi bO JQcJfi hdgG GSGdJc MGLI aCfJ JgJR dgG s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B152s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(1/ 780) s
Keywords: (3GdCOHs